Change in Body Size and Mortality: Results from the Melbourne Collaborative Cohort Study - Karahalios, Amalia; Simpson, Julie A.; Baglietto, Laura; MacInnis, Robert J.; Hodge, Allison M.; Giles, Graham G.; English, Dallas R. (PloS one, 2014)
The association between change in weight or body mass index, and mortality is widely reported, however, both measures fail to account for fat distribution. Change in waist circumference, a measure of central adiposity, in relation to mortality has not been studied extensively. We investigated the association between mortality and changes in directly measured waist circumference, hips circumference and weight from baseline (1990-1994) to wave 2 (2003-2007) in a prospective cohort study of people aged 40-69 years at baseline. Cox regression, with age as the time metric and follow-up starting at wave 2, adjusted for confounding variables, was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for change in body size in relation to mortality from all causes, cardiovascular disease and cancer. There were 1465 deaths (109 cancer, 242 cardiovascular disease) identified during an average 7.7 years of follow-up from 21 298 participants. Compared to minimal increase in body size, loss of waist circumference (HR: 1.26; 95% CI: 1.09-1.47), weight (1.80; 1.54-2.11), or hips circumference (1.35; 1.15-1.57) were associated with an increased risk of all-cause mortality, particularly for older adults. Weight loss was associated with cardiovascular disease mortality (2.40; 1.57-3.65) but change in body size was not associated with obesity-related cancer mortality. This study confirms the association between weight loss and increased mortality from all-causes for older adults. Based on evidence from observational cohort studies, weight stability may be the recommended option for most adults, especially older adults.